Identification of Bacillus anthracis Strains from Animal Cases in Ethiopia and Genetic Characterization by Whole-Genome Sequencing - Abebe Olani; Domenico Galante; Matios Lakew; Bayeta Senbeta Wakjira; Getnet Abie Mekonnen; Tesfaye Rufael; Tsegaye Teklemariam; Wondwosen Kumilachew; Shimalis Dejene; Ayele Woldemeskel; Adanech Wakjira; Getachew Abichu; et al. (Pathogens)
Anthrax is a zoonotic disease characterized by rapid onset with usual fatal outcomes in livestock and wildlife. In Ethiopia, anthrax is a persistent disease; however, there are limited data on the isolation and molecular characterization of Bacillus anthracis strains. This study aimed to characterize B. anthracis isolated from animal anthrax outbreaks between 2019 and 2024, from different localities in Ethiopia. B. anthracis was identified using standard microbiology techniques and confirmed by real-time PCR. For the first time in Ethiopia, the genetic diversity of five Bacillus anthracis strains, isolated from dead cattle and goats, was investigated by Whole Genome Sequencing (WGS) and bioinformatics analyses. The five sequenced strains were compared to one Ethiopian B. anthracis genome and the other 29 B. anthracis genomes available in the global genetic databases to determine their phylogeny. The genomes of the strains were also analyzed to detect the presence of antimicrobial resistance and virulence genes. The whole genome SNP analysis showed that the Ethiopian B. anthracis strains were grouped in the A clade. Three strains (BA2, BA5, and BA6) belonged to the A.Br.034 subgroup (A.Br.005/006), and two strains (BA1 and BA4) belonged to the A.Br.161 (Heroin) clade of the Trans-Eurasian (TEA) group. The findings of this study will contribute to expanding the current understanding of the anthrax hotspots in Ethiopia, and the phylogenetic correlation and/or diversity of the circulating strains.